2010
DOI: 10.1088/0004-637x/717/1/245
|View full text |Cite
|
Sign up to set email alerts
|

Supernova Light Curves Powered by Young Magnetars

Abstract: We show that energy deposited into an expanding supernova remnant by a highly magnetic (B ∼ 5 × 10 14 G) neutron star spinning at an initial period of P i ≈ 2 − 20 ms can substantially brighten the light curve. For magnetars with parameters in this range, the rotational energy is released on a timescale of days to weeks, which is comparable to the effective diffusion time through the supernova remnant. The late time energy injection can then be radiated without suffering overwhelming adiabatic expansion losses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
979
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 794 publications
(1,012 citation statements)
references
References 31 publications
29
979
3
1
Order By: Relevance
“…We think of this as macrophysical uncertainties, e.g., a clumpy density distribution. Radiation hydrodynamic calculations show that the magnetardriven ejecta pile up at some radius (Kasen & Bildsten 2010), rather than homogeneously distributed, as assumed in this work.…”
Section: Discussionmentioning
confidence: 66%
“…We think of this as macrophysical uncertainties, e.g., a clumpy density distribution. Radiation hydrodynamic calculations show that the magnetardriven ejecta pile up at some radius (Kasen & Bildsten 2010), rather than homogeneously distributed, as assumed in this work.…”
Section: Discussionmentioning
confidence: 66%
“…Expanding upon this and a number of authors have suggested that magnetars may power superluminous type II and Ibc SNe (Thompson et al 2004;Woosley 2010;Kasen & Bildsten 2010;Gal-Yam 2012;Quimby et al 2011); indeed the 7.29 M progenitor model of Woosley (2010) is directly motivated by the presence of J1647-45 within Wd1. Moreover, Inserra et al (2013) studied the late-time lightcurves of five superluminous type Ic SNe, finding that the data are indeed consistent with these events being powered by the rapid spin-down of newly born magnetars (see also McCrum et al 2013;Nicholl et al 2013) Additionally, magnetars have also been proposed as the central engines of some gamma-ray bursts (GRBs; e.g.…”
Section: Discussionmentioning
confidence: 76%
“…The spin-down power of a newly formed magnetar can create a brighter and faster evolving SN light curve than radioactive decay (Piro & Ott 2011). This mechanism can contribute to the extreme peak luminosity of Type Ib/c and super-luminous SNe (Woosley 2010;Kasen & Bildsten 2010;Chatzopoulos et al 2012). In this case, (t) includes radioactive energy production as well as magnetar spin-down: where Ni (t) is the energy production rate of radioactive decay of nickel and cobalt as defined in the previous section and M (t) is the energy production rate of the spin-down per unit mass.…”
Section: Magnetar Spin-downmentioning
confidence: 99%